Socio-demographic characteristics of patients with diagnosed functional dyspepsia - Piotrowicz, Grażyna; Stępień, Beata; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction : The term "dyspepsia" comes from the Greek words "dys' and 'peptin", which maen "ill digestion" or indigestion, although this set of symptoms in the adult clinic has little to do with the digestion or absorption process, and refers more to ailments related to the upper section of the gastrointestinal tract. Aim : Assessment of the frequency of functional dyspepsia diagnosis, the characteristics of the group and an attempt to identify the accompanying symptoms, assessment of histological lesions and an attempt to answer question about the efficiency of anti-secretory and eradication therapy. Material and methods : The study involved patients reporting for gastrofiberscopic examination due to dyspeptic ailments. A total of 230 patients were examined, including 140 women and 90 men, above 18 years of age. They underwent endoscopic examination, and a selected group with functional dyspepsia (FD), analysed using the ‘Gast’ questionnaire, underwent eradication therapy or proton pump inhibitors. Statistical analysis involved χ 2 and Fischer’s test. Results : The study involved 230 individuals with dyspeptic disorders. The largest age group was 46–60 years. These patients reported due to their ailments mostly in autumn and winter. The differentiated group with FD included 53 patients (23% of the clinical population). 69.8% of the FD group was infected with Helicobacter pylori (with 81.2% of the whole population, respectively). Individuals with FD reported improvement more often after being administered drugs to decrease gastric secretion, more often declared post-elementary education and suffered from non-gastric ailments yet still described their state of health as good. No positive therapeutic effect of eradication was noticed during the 6-month observation. Conclusions : Due to the very high ratio of subjects with functional dyspepsia, also observed in the study sample, and the influence of civilization progress, we should expect increasing frequency of occurrence of this problem.